Capacity calculation of a packet switched voice cellular network - Samaras, K.; Demetrescu, C.; Luschi, C.; Ran Yan (VTC2000-Spring. 2000 IEEE 51st Vehicular Technology Conference Proceedings (Cat. No.00CH37026), 2000)
A semi-analytical method for the calculation of the teletraffic capacity of a packet switched voice cellular network is provided. The capacity is defined as the maximum traffic load that can be accommodated subject to certain service quality criteria and can be limited either by co-channel interference levels or by the number of available traffic channels. Focusing on GSM-type systems it is demonstrated that there is a potential for a significant capacity improvement when packet switching is used instead of circuit switching over the air interface, due to the inherent statistical multiplexing gain associated with packet switching.